2007
DOI: 10.1007/s00300-007-0256-4
|View full text |Cite
|
Sign up to set email alerts
|

Food choice of Antarctic soil arthropods clarified by stable isotope signatures

Abstract: Antarctic soil ecosystems are amongst the most simplified on Earth and include only few soil arthropod species, generally believed to be opportunistic omnivorous feeders. Using stable isotopic analyses, we investigated the food choice of two common and widely distributed Antarctic soil arthropod species using natural abundances of 13 C and 15 N and an isotope labelling study. In the laboratory we fed the isotomid springtail Cryptopygus antarcticus six potential food sources (one algal species, two lichens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…3), indicating improved feeding conditions (cf. Hodkinson and Wookey 1999;Bokhorst et al 2007b). In spite of differences in physicochemical soil parameters and vegetation structure being reported between the ornithogenic tundra developing close to planktivorous and piscivorous seabird colonies (Stempniewicz et al 2006), we found similar abundance and species composition of springtail communities in the sampling plots influenced by the two representatives of these colony types examined in this study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…3), indicating improved feeding conditions (cf. Hodkinson and Wookey 1999;Bokhorst et al 2007b). In spite of differences in physicochemical soil parameters and vegetation structure being reported between the ornithogenic tundra developing close to planktivorous and piscivorous seabird colonies (Stempniewicz et al 2006), we found similar abundance and species composition of springtail communities in the sampling plots influenced by the two representatives of these colony types examined in this study.…”
Section: Discussionsupporting
confidence: 54%
“…Cragg and Bardgett 2001;Hodkinson et al 2002;Hopkin 2002;Bokhorst et al 2007b). Invertebrates perform and regulate mineralization of fresh organic residues, mostly acting in their physical breakdown or as grazers of the microflora, whereas microorganisms are responsible for the chemical degradation of complex molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This would to some extent be in contradiction to our results, where springtails and oribatid mites obviously did not depend on adjacent vascular plants. One possible explanation for the persistence of springtails in bare-soil habitats is their euryoecious feeding behavior, consuming unicellular algae, fungal mycelium, and lichens as well as plant litter and living plants (Bokhorst et al 2007;Hodkinson et al 1996; Minor al. 2016).…”
Section: Microarthropodsmentioning
confidence: 99%
“…A functional relationship between lichen biomass and the diversity of food sources for different animals was pointed out by several authors (Bokhorst et al 2007;Llano 2012;Liu et al 2013;Norris et al 2011). Common intracellular products occurring in lichens include amino acids and proteins, polysaccharides and polyols, carotenoids and vitamins (Elix 1996).…”
Section: Food Provisionmentioning
confidence: 93%